Difference in Frequency and Distribution of Nodal Metastases Between Intermediate and High Risk Prostate Cancer Patients: Results of a Superextended Pelvic Lymph Node Dissection - Roscigno, Marco; Nicolai, Maria; La Croce, Giovanni; Pellucchi, Federico; Scarcello, Manuela; Saccà, Antonino; Angiolilli, Diego; Chinaglia, Daniela; Da Pozzo, Luigi F. (Frontiers in Surgery, 2018)
OBJECTIVES: To describe the frequency and distribution of metastases to pelvic nodes, in patients (pts) with clinically localised, intermediate-high risk prostate cancer (PCa), treated with radical prostatectomy (ORP) and superextended pelvic lymph node dissection (sePLND). PATIENTS AND METHODS We retrospectively evaluated 630 consecutive pts with clinically localized, intermediate-high risk PCa, treated with ORP and sePLND between 2009 and 2016 at a single institution. The sePLND always consisted of the external iliac, obturator, internal iliac, presacral and common iliac sites. RESULTS LN+ were found in 133 patients (21.1%). The median number of removed nodes and LN+ was 25 and 1, respectively. LN+ were found in 58 (43.6%), 53 (39.8%), 64 (48.1%), 16 (12%) and 20 (15%) and were present as a single site in 22 (16.5%), 20 (15%), 27 (20.3%), 0, and 6 (4.5%) cases in the external iliac, obturator, internal iliac, common iliac, and presacral chain, respectively. An ePLND would have correctly staged 127 (95%) pts but removed all LN+ in only 97 (73%) pts. Presacral nodes harbored LN+ in 18 high risk pts out of 20 cases. Moreover, all but 1 pts with common iliac LN+ were in high risk group. CONCLUSIONS These results suggest that removal of presacral and common iliac nodes could be safely omitted in intermediate risk pts. However, a PLND limited to external iliac, obturator and internal iliac region should be adequate for nodal staging purpose, but not enough accurate if we aim to remove all possible site of LN+ in high risk pts.